PERBEDAAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA SEBELUM DAN SESUDAH PENERIMAAN PENYULUHAN KESEHATAN TENTANG KEBUTUHAN SEKSUAL DI SMA MUHAMMADIYAH 3 JEMBER - Hendra Dwi Cahyono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
Adolescent is a period of transition between childhood and adult stages. Physical changes that occur in adolescence led to the emergence of sexual interest and curiosity is high on sexuality. The purpose of this study was to determine differences in the level of knowledge and attitudes about adolescent sexual counseling before and after the acceptance of sexual needs in SMA Muhammadiyah Jember 3. This type of research used in this study was Quasi Experiment (quasi-experimental) with the design of one-group pre-test post-test design, where the level of students' knowledge and attitudes regarding sexual needs were measured before and after treatment are given in the form of health education / counseling. The population in this study is a Class XI student at SMA Muhammadiyah Jember totaled 3 152 people consisting of grade social studies and language. The sample size in this study was 60 with a sampling technique used was purposive sampling. Research before giving counseling to determine the level of knowledge about the category (88.3%), sufficient (11.7%). Negative attitudes (85%), positive (15%). After the provision of information to determine the level of knowledge both categories (3.3%), adequate (55%), and less (41.7%). Negative attitudes (60%), positive (40%). Based on the Wilcoxon test were analyzed using SPSS obtained significance value (Asymp. Sig) between the level of knowledge before and after the extension of 0000> 0.05, meaning that there is a significant difference between the level of knowledge before (pretest) and after (posttest) was given counseling. The conclusion of this study is there are different levels of knowledge and attitudes of adolescents before and after receipt of counseling in IPS-grade students at SMA Muhammadiyah Jember 3